Інноваційна політика, як об’єкт фінансово-правового забезпечення - Денисов, А. І.; Denysov, A. I.; ORCID: https://orcid.org/0000-0002-6256-0172 (Міжнародний науковий журнал "Інтернаука". Серія : Юридичні науки. - 2020. - № 5(27). - С. 9-14, 2020)
Досліджено основні концептуальні підходи до визначення феноменів державної політики в цілому та державної інноваційної політики. Наголошено на необхідність внесення змін до вітчизняного законодавства у сфері регулювання інноваційної політики держави, оскільки воно не містить визначення державної інноваційної політики, а також однобоко підходить до здійснення державної інноваційної політики, не розкриваючи його у контексті обмеження розробки, впровадження та використання інновацій у виробництві продукції та/або надання послуг. Визначено необхідність створення дієвого механізму обмеження розробки, впровадження та використання інновацій, які загрожують національній безпеці. Запропоновано створити вичерпний перелік таких інновацій, а також перелік засобів фінансово-правового забезпечення обмеження їх розробки, впровадження та використання. Підкреслено важливість розроблення на концептуальному рівні єдиної правової позиції щодо функціонування цілісного фінансово-правового механізму забезпечення державної інноваційної безпеки та прийняття стратегії захисту національної інноваційної безпеки на державному рівні.

The article explores the main conceptual approaches to the definition of the phenomena of state policy in general and state innovation policy. It is established that in the domestic legislation there is no definition of state national policy. The basic principles and goals of the state innovation policy set in Art. 3 of the Law of Ukraine «On innovation» and concluded that it is necessary to supplement this norm. It is concluded that in the scientific literature there is no unified approach to the definition of state policy = and state innovation policy. The article explores the purpose and principles of state innovation policy defined by law. It is proposed to supplement the existing list of principles with such a principle as the orientation of the state innovation policy to ensure national economic and environmental security. Attention is drawn to the need to amend domestic legislation in the field of regulation of the state’s innovation policy, since it does not contain a definition of state innovation policy, and also takes a one-sided approach to implementing state innovation policy without disclosing it in the context of restricting the development, implementation and use of innovations in the production of products and/or the provision of services. In particular, the need to create an effective mechanism to limit the development, implementation and use of innovations that threaten national security is noted. It is proposed to create an exhaustive list of such innovations, as well as a list of financial and legal support to limit their development, implementation and use. The importance of developing at the conceptual level a unified legal position regarding the functioning of a holistic financial and legal mechanism for ensuring state innovation security and adopting a strategy for protecting national innovation security at the state level was emphasized.

Исследованы основные концептуальные подходы к определению феноменов государственной политики в целом и государственной инновационной политики. Указано на необходимость внесения изменений в отечественное законодательство в сфере регулирования инновационной политики государства, поскольку оно не содержит определения государственной инновационной политики, а также однобоко подходит к осуществлению государственной инновационной политики, не раскрывая его в контексте ограничения разработки, внедрения и использования инноваций в производстве продукции и/или предоставления услуг. В частности, отмечается необходимость создания действенного механизма ограничения разработки, внедрения и использования инноваций, которые угрожают национальной безопасности. Предложено создать исчерпывающий перечень таких инноваций, а также перечень средств финансово-правового обеспечения ограничения их разработки, внедрения и использования. Подчеркнута важность разработки на концептуальном уровне единой правовой позиции относительно функционирования целостного финансово-правового механизма обеспечения государственной инновационной безопасности и принятия стратегии защиты национальной инновационной безопасности на государственном уровне.
Innovative policy as an object of financial and legal support
Инновационная политика, как объект финансово-правового обеспечения
Денисов, А. І. Інноваційна політика, як об’єкт фінансово-правового забезпечення [Електронний ресурс] / Денисов Андрій Ігорович // Міжнародний науковий журнал "Інтернаука". Серія : Юридичні науки. - 2020. - № 5(27). - С. 9-14.- Режим доступу: http://nbuv.gov.ua/UJRN/mnjiu_2020_5_3.
Keywords: Фінансове право. Бюджетне право. Банківське право. Financis Law. Budget Law. Banking Law. Финансовое право. Бюджетное право. Банковское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; інноваційна політика; innovative policy; инновационная политика; фінансово-правове забезпечення; financial and legal support; финансово-правовое обеспечение; державна політика; state policy; государственная политика; національна безпека; national security; национальная безопасность